The geography and economics of forgoing medical examinations or therapeutic treatments in Italy during the economic crisis - Alessio Petrelli; Aldo Rosano; Alessandra Rossi; Concetta Mirisola; Cesare Cislaghi (BMC, 2019)
Abstract Background In Italy, the number of individuals who have forgone medical examinations or treatments for economic reasons is one of the highest in Europe. During the global economic crisis of 2008, the restrictive policies concerning access to healthcare and the quality of these services, which differs widely throughout the country, may have accentuated the territorial differences in unmet needs, thereby penalizing the more disadvantaged segments of the population. The study aimed at evaluating the geographical and socioeconomic differences, in particular the risk of poverty, that influence forgoing healthcare services in Italy. Methods Cross-sectional Italian data from the 2004-2015 European Survey on Income and Living Conditions (EU-SILC) were used. Hierarchical logistic models were tested, using as the outcome unmet needs for medical examinations or treatment in the preceding 12 months, and as risk factor the condition of being at risk of poverty. Age, sex, citizenship, educational level, presence of chronic or severely limiting diseases and self-perceived health were used as adjustment factors. Analyses were stratified over three time periods: pre-crisis (2004-2007), initial phase of the crisis (2008-2012) and second phase of the crisis (2013-2015). Results In Central Italy and particularly in Southern Italy, a marked increase (9.9% in 2013-2015) was seen in the overall rate of unmet needs as well as in that of unmet needs due to economic reasons. The probability of unmet needs was higher, and increased over time, for those at risk of poverty (aOR = 1.54 in 2004-07, aOR = 1.70 in 2008-12, aOR = 2.21 in 2013-15). Individuals with a low educational level, who had a chronic or severely limiting disease, who perceived their health as not good and immigrants had a higher risk of forgoing healthcare. The regions in Southern Italy had a significantly higher probability of unmet needs. Conclusions A strong association was found between the probability of forgoing medical examination or treatment and being at risk of poverty. Study results underline the need for healthcare policies aimed at facilitating access to healthcare services, particularly in the South, by developing a progressive mechanism of contribution to healthcare costs proportional to income and by guaranteeing free access to the poor.